Benefícios da prática de yoga nidra para a qualidade de vida e do sono: etnografia em um grupo terapêutico - Mion, Daniela Gardenal (Universidade Federal de São Carlos, 2025)
Introduction: This study understands that symptoms such as stress, sadness, anxiety, insomnia, and dissatisfaction with life may reflect broader social dynamics inherent to contemporary ways of living and have a direct impact on the decrease in quality of life. Traditional medicines and integrative practices encompass vitalist approaches and therapeutic methods that foster healthier relationships with oneself and society, promote self-care, and support comprehensive health restoration. Yoga nidra, an Indian technique of deep relaxation, has been used to promote physical, mental, and emotional balance, contributing to self-awareness, overall quality of life, and, specifically, sleep quality. Objectives: To analyze the benefits associated with the practice of yoga nidra for quality of life and to investigate participants’ perceptions of changes in quality of life and sleep after seven in-person sessions. Methodology: This is a mixed-methods study employing a qualitative approach grounded in ethnography and a quantitative approach based on simple statistical analysis. The study was conducted by monitoring a therapeutic group at a specialized health service of a public Brazilian university. Data were collected through participant observation, field diary records, a final evaluation questionnaire, registration of personal and health data, and the Pittsburgh Sleep Quality Index (PSQI) protocol administered before and after seven weekly sessions. Inclusion criteria required attendance in at least four sessions and completion of the PSQI at both mandatory times. The sessions incorporated guided yoga nidra practices, the use of essential oils, and moments of group sharing. Results and Discussion: The group consisted of eight adult participants with diverse previous experiences and demands related to anxiety, insomnia, physical tension, and emotional overload. A reduction in the average PSQI score was observed, indicating a shift from poor to moderate sleep quality within the group, suggesting a modest improvement in sleep quality. Participants reported learning about self-care and interpersonal relationships, emotional awareness, anxiety reduction, preparing the environment and mental state for sleep, and the therapeutic use of essential oils. The observed benefits suggest a positive impact on overall quality of life, reflecting greater emotional balance, increased bodily awareness, and the incorporation of new strategies into daily life. These findings are aligned with international literature that highlights the positive effects of yoga nidra on stress, anxiety, and depression, indicating that the practice may enhance individuals’ capacity to cope with life’s demands. Conclusion: The practice of yoga nidra within a therapeutic group proved to be an effective integrative practice, promoting relaxation, well-being, and improved sleep quality. The results demonstrate its potential as a complementary resource for comprehensive care, expanding possibilities for self-care and health promotion. The study indicates the need for further investigations in the Brazilian context to deepen the understanding of the effects of yoga nidra.
Benefits of yoga nidra for quality of life and sleep: ethnographic study in a therapeutic group
Keywords: Terapias Complementares; Promoção da Saúde; Pesquisa Etnográfica; Yoga; Saúde Integral; Saúde Mental; Complementary Therapies; Health Promotion; Ethnographic research; Yoga; Holistic Health; Mental Health; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar